Empowering Women Entrepreneurs through Affirmative Action: Implications for Innovation and Sustainable Performance in Indonesia’s Creative Industries - Maulidina, Siti Handayani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
In highly competitive and rapidly evolving industries, achieving and sustaining organizational success requires continuous innovation, adaptability, and strategic inclusiveness. Within Indonesia’s digital creative sector, organizations are increasingly challenged to generate novel ideas, develop unique processes, and deliver innovative products that ensure differentiation and long-term competitiveness in both domestic and global markets. This study investigates the influence of affirmative action supporting women’s entrepreneurship on creativity, innovation, and overall performance within Indonesia’s creative industries. The research draws on a population of 2,876 individuals actively engaged in various segments of the creative economy, from which 350 respondents were purposively selected to obtain relevant and representative insights. Utilizing a quantitative research design, the study employs structural analysis to examine both the direct and indirect effects of women’s affirmative action initiatives on innovation capacity and organizational outcomes. The findings reveal that empowering women entrepreneurs exerts a significant and positive effect on innovation and firm performance. Moreover, innovation functions as a mediating variable that enhances the contribution of women’s entrepreneurial participation toward sustainable industry development. These results emphasize the strategic importance of gender-inclusive policies and entrepreneurial empowerment as key drivers of creativity, innovation, and competitiveness. Strengthening women’s roles in entrepreneurship not only elevates individual and organizational capabilities but also fosters social inclusion and accelerates economic transformation. Ultimately, the study underscores that empowering women in the creative sector contributes to building a more resilient, innovative, and sustainable creative economy in Indonesia.